2022
DOI: 10.3892/ijo.2022.5365
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin inhibits colon cancer cell apoptosis and decreases chemosensitivity to 5‑FU by promoting the SDF‑1/CXCR4/Akt axis

Abstract: 5-Fluorouracil (5-FU) is the preferred chemotherapeutic drug used in the treatment of colon cancer; however, drug resistance affects its clinical efficacy. Visfatin, an adipokine that promotes tumour development, has the potential to increase resistance to chemotherapy. The present study aimed to verify the effects of visfatin on the sensitivity of colon cancer cells to 5-FU and to elucidate the potential mechanisms involved. Tissue microarrays (TMAs) were used to analyse visfatin differential expression in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…Conversely, the inhibitory effect of VIS was documented in studies on mouse and rat pancreatic cell lines, rat hippocampal cells, and a colon cancer cell line [28,[30][31][32]. Furthermore, VIS was observed to exhibit an anti-apoptotic effect by increasing the gene/protein expression of Bcl-2 and decreasing the gene/protein expression of cellular tumor antigen p53 (a key regulator of apoptosis that promotes cell death after extensive DNA damage), cytochrome c (a factor that mediates activation of the intrinsic pathway of apoptosis), and caspase 3 [43,45,[47][48][49]. The results obtained in this study suggest that VIS does not trigger cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the inhibitory effect of VIS was documented in studies on mouse and rat pancreatic cell lines, rat hippocampal cells, and a colon cancer cell line [28,[30][31][32]. Furthermore, VIS was observed to exhibit an anti-apoptotic effect by increasing the gene/protein expression of Bcl-2 and decreasing the gene/protein expression of cellular tumor antigen p53 (a key regulator of apoptosis that promotes cell death after extensive DNA damage), cytochrome c (a factor that mediates activation of the intrinsic pathway of apoptosis), and caspase 3 [43,45,[47][48][49]. The results obtained in this study suggest that VIS does not trigger cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [8] reported that visfatin stimulates proliferation, and inhibits apoptosis of, endometrial carcinoma in both Ishikawa and KLE cells. Furthermore, visfatin may promote proliferation and inhibit apoptosis of colon and breast cancer cells [9,19]. PARP is one of the best known substrates for caspase activity, and PARP cleavage to yield fragments of 89 and 24 kDa is a universally accepted hallmark of apoptosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Visfatin, such as leptin, is another adipokine that supports colorectal carcinogenesis through different signaling pathways activation, such as ERK1/2, p38 MAPK, PI3K/mTOR, JNK, and JAK/STAT, which promote cell proliferation and metastasis [ 79 ]. In addition, a recent study revealed that visfatin also acts as an inhibitor of the 5-fluorouracil (5-FU) therapeutic effect in CRC patients through visfatin/SDF-1/Akt pathway activation ( Table 1 ) [ 80 ].…”
Section: The Caas Role In Crc Progressionmentioning
confidence: 99%
“…Radical surgery associated with chemotherapy is the conventional treatment in CRC cases, 5-FU being the most common used drug in the advanced stages of the disease. Several mechanisms are currently related to 5-FU chemoresistance and treatment failure in CRC, such as Bcl-2 and Bcl-xL overexpression in cancer cells, p53 gene mutations, 5-FU efflux induced by the increased expression of the ATP-binding cassette transporter, nucleoside metabolizing enzymes overexpression, along with mismatch repair system disruption [ 80 ]. Adipocytes and CAAs-derived visfatin have been shown to reduce the sensitivity to 5-FU through SDF-1/CXCR4 pathway activation ( Table 2 ) [ 80 ].…”
Section: The Caas Role In Crc Progressionmentioning
confidence: 99%
See 1 more Smart Citation